2011
DOI: 10.1093/humrep/der072
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic sigmoid resection with transrectal specimen extraction: a novel technique for the treatment of bowel endometriosis

Abstract: Full laparoscopic sigmoid resection reduced operating times and decreased post-operative VAS-scores and analgesic requirements compared with the conventional laparoscopic sigmoid resection for bowel endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
1
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 33 publications
0
34
1
1
Order By: Relevance
“…There was higher risk of developing SSI in the transanal approach than in the transverse incision approach [53] for specimen retrieval (Table 4). One study [54] reported specimen retrieval through the stoma site in comparison with a transanal approach, and reported no difference in SSI.…”
Section: Resultsmentioning
confidence: 99%
“…There was higher risk of developing SSI in the transanal approach than in the transverse incision approach [53] for specimen retrieval (Table 4). One study [54] reported specimen retrieval through the stoma site in comparison with a transanal approach, and reported no difference in SSI.…”
Section: Resultsmentioning
confidence: 99%
“…Each subscale has a set of 4-point categorical rating items and one overall assessment item. The number of questions in each subscale determines the score range as follows: appearance (9-36), symptoms (6-24), consciousness (6-24), satisfaction with appearance (8-32) and satisfaction with symptoms (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). The overall assessment score ranges from 1 to 5 for appearance and symptoms and from 1 to 4 for the remaining three subscales.…”
Section: Patient Scar Assessment Questionnairementioning
confidence: 99%
“…A specimen eltávolítása után a distalis bélvég varrógéppel lezárható. A proximalis bélvégbe laparoszkóposan dohányzacskóöl-tést helyezve, a varrógép fejének behelyezése után, az anastomosis a szokott módon intracorporalisan elvégez-hető [2] (3. ábra). Ezt a módszert 120, bélendometri-osis miatt végzett multidiszciplinárisan laparoszkópos műtétből 5 alkalommal alkalmaztuk.…”
Section: Transrectalis Specimeneltávolítás Endometriosis Miatt Végzetunclassified